2019
DOI: 10.1111/sms.13606
|View full text |Cite
|
Sign up to set email alerts
|

Submaximal field testing validity for aerobic fitness assessment in recreational football

Abstract: Submaximal field tests are especially recommended when repeated testing is warranted. This study aimed at assessing the validity of the submaximal versions of the Yo‐Yo intermittent tests in male recreational football players in untrained and trained status. The participants’ (n = 66; age 39.3 ± 5.8 years, VO2max 41.2 ± 6.2 mL·kg−1·min−1, body mass 81.9 ± 10.8 kg, height 173.2 ± 6.4 cm) heart rate after 2 minutes (HR2min) during the level 1 (YYIE1HR2min) and 2 (YYIE2HR2min) versions of the Yo‐Yo intermittent e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Yo-Yo test has a higher ecological validity and reliability (Castagna et al, 2019;Francini et al, 2019), since soccer matches performance analyses have shown that >90% of all sprints in games are shorter than 20 m, acceleration and deceleration capabilities are essential for soccer athletes (Modric et al, 2019). Still, the importance of peak velocity increases during the game when sprints start from a jogging or non-stationary condition (Datson et al, 2014;Palucci Vieira et al, 2019;Slimani and Nikolaidis, 2019), with the Yo-Yo intermittent test being useful to evaluate the physical fitness condition of soccer players in terms of levels (Redkva et al, 2018;Povoas et al, 2020;Castagna et al, 2020b), gender (Emmonds et al, 2019;Castagna et al, 2020a), and age classes (Ehlert et al, 2019;Francini et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yo-Yo test has a higher ecological validity and reliability (Castagna et al, 2019;Francini et al, 2019), since soccer matches performance analyses have shown that >90% of all sprints in games are shorter than 20 m, acceleration and deceleration capabilities are essential for soccer athletes (Modric et al, 2019). Still, the importance of peak velocity increases during the game when sprints start from a jogging or non-stationary condition (Datson et al, 2014;Palucci Vieira et al, 2019;Slimani and Nikolaidis, 2019), with the Yo-Yo intermittent test being useful to evaluate the physical fitness condition of soccer players in terms of levels (Redkva et al, 2018;Povoas et al, 2020;Castagna et al, 2020b), gender (Emmonds et al, 2019;Castagna et al, 2020a), and age classes (Ehlert et al, 2019;Francini et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The test was terminated when the subjects failed twice to reach the starting line, or the participant felt unable to complete another shuttle at the dictated speed (Castagna et al, 2020b). The VO 2 max (ml/kg/min) was assessed as indicated in Povoas et al (2020) study.…”
Section: Procedures and Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of VO 2max on fitness and health promoted the interest in valid, reliable and sustainable alternative methods to CPET to estimate VO 2max . Field testing, namely the Yo-Yo intermittent tests, were recently proposed as valid, reliable and practically sustainable tools for estimating individual VO 2max in recreational football players (Castagna et al 2020;Póvoas et al 2019a). However, CPET and field tests both require participants' maximal effort to obtain valid and satisfactory VO 2max estimates.…”
Section: Introductionmentioning
confidence: 99%
“…Exhaustive efforts may represent a concern when patients enroll in a training intervention if they have a previous inactive or untrained status and in the presence of chronic morbidity(ies). Alternatively, submaximal field testing may represent a valid and reliable surrogate for exhaustive testing (Póvoas et al 2019a). However, patients may experience difficulties in adapting to submaximal testing given their reduced familiarisation with testing and their current fitness and health status.…”
Section: Introductionmentioning
confidence: 99%